Empedocles’ Big Break: Pre-Socratic Cosmology and The Big Bounce - Preston, David (Sapiens ubique civis, 2021)
This paper endeavours to demonstrate that certain strands of ancient and modern cosmological thought are not as dissimilar as one might initially believe. In doing so, it will examine two accounts of the fundamental nature and origin of the universe – one put forward in the 5th century BCE by the Pre-Socratic Empedocles, and one favoured by a faction of 21st Century CE physical cosmologists. After said parallels are highlighted, there will be some speculation on how Empedocles may have arrived at such conclusions two and a half millennia ago, followed by a defence of him being classified only as an ancient poet.